2019
DOI: 10.3982/qe711
|View full text |Cite
|
Sign up to set email alerts
|

On uniform asymptotic risk of averaging GMM estimators

Abstract: This paper studies the averaging GMM estimator that combines a conservative GMM estimator based on valid moment conditions and an aggressive GMM estimator based on both valid and possibly misspecified moment conditions, where the weight is the sample analog of an infeasible optimal weight. We establish asymptotic theory on uniform approximation of the upper and lower bounds of the finite-sample truncated risk difference between any two estimators, which is used to compare the averaging GMM estimator and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Very recently,Zhang and Yu (2018) andLam and Souza (2019) proposed combining spatial weight matrices in recognition of possible misspecification of the weight matrix andCheng et al (2019) suggested combining a conservative GMM estimator based on valid moment conditions and an aggressive GMM estimator based on both valid and possibly misspecified moment conditions.…”
mentioning
confidence: 99%
“…Very recently,Zhang and Yu (2018) andLam and Souza (2019) proposed combining spatial weight matrices in recognition of possible misspecification of the weight matrix andCheng et al (2019) suggested combining a conservative GMM estimator based on valid moment conditions and an aggressive GMM estimator based on both valid and possibly misspecified moment conditions.…”
mentioning
confidence: 99%
“…We consider this a small and acceptable price to pay to avoid the risk of bias and higher RMSE that occurs under uncorrected MLM in the presence of correlated random effects. Accordingly, we suggest these unbiased approaches rather than any approach that seeks to mix estimators (e.g., Cheng, Liao, and Shi 2019) or to choose between FE (or bcMLM) and uncorrected MLM based on some criterion. For example, we do not advocate for choosing uncorrected MLM when the number of observations per group is above some threshold: one cannot know how many observations will be enough for the bias (and RMSE) to become acceptably small, and any potential efficiency or accuracy gain of MLM relative to FE is diminishing in group size anyway.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, our approach is related to recent work on characterizing various policy relevant treatment effects as weighted averages of the marginal treatment effect, for example, Heckman and Vytlacil (2005), Heckman, Urzua, and Vytlacil (2006), Brinch, Mogstad, and Wiswall (2017), Mogstad, Santos, and Torgovitsky (2018), Andrews (2019), Evdokimov and Kolesár (2018), and Słoczyński (2018). Since these examples cannot be handled by a local misspecification framework (e.g., Cheng, Liao, and Shi (2019)), our approach is complementary to local misspecification.…”
Section: Introductionmentioning
confidence: 99%
“…This is a particularly difficult yet important topic. The methods of Cheng, Liao, and Shi (2019) may be useful in this regard.…”
Section: Introductionmentioning
confidence: 99%